PEMIKIRAN KH. ACHMAD SIDDIQ TENTANG RELASI AGAMA DAN NEGARA DI INDONESIA: KH. Achmad Siddiq’s Thoughts On The Relationship Between Religion And State - Mohammad Haris Taufiqur Rahman; M. Noor Harisudin (UIN Kiai Haji Achmad Siddiq Jember, 2023)
The relationship between religion and the state is a subject that always exists to be studied, especially in the very diverse country of Indonesia. Pancasila is a big idea that is capable of bringing Indonesia independence, not only that, Pancasila is the basis of State philosophy, State ideology and at the same time the main source of all decisions and laws in the State of Indonesia. Pancasila is also able to become a link between the tensions that occur between groups supporting religion and the state. Until the figure of a cleric and umara appeared who was able to defuse the conflict between religion and the state, namely KH. Ahmad Siddiq. KH. Achmad Siddiq as a charismatic Kiai figure belonging to Nahdlatul Ulama is able to become a star who can unite and harmonize relations between religion and the state. From his brilliant thinking, Pancaila was finally accepted as the sole principle of the state. The type of research used is literature, which focuses and limits its activities to literature to obtain data without conducting research in the field. This research concluded; 1)KH. Achmad Siddiq was able to become a figure who could hypnotize Muslims, especially Nahdliyin residents, to accept Pancasila as the sole principle of the organization and state. This is a reference for religious communities (Islam), especially NU citizens in the state. 2) Regarding the concept of the relationship between religion and the state in Indonesia, it is known as the Tri Ukhuwah concept. First, Ukhuwwah Islamiyah, namely a brotherhood that grows and develops because of security or religious similarities, both at the national and international levels. Second, Ukhuwah Wataniyyah, namely a ukhuwah that grows and develops on the basis of a sense of nationalism. Third, Ukhuwwah Insaniyah (basyariyyah), namely ukhuwah that grows and develops on the basis of humanity. ABSTRAK Hubungan agama dan negara menjadi sebuah kajian yang selalu eksis untuk dikaji, apalagi di negara Indonesia yang sangat majemuk. Pancasila merupakan gagasan besar yang mampu membawa Indonesia merdeka, tidak hanya itu Pancasila merupakan sebuah dasar falsafah Negara, ideologi Negara dan sekaligus sumber utama dari segala sumber keputusan dan hukum di Negara Indonesia. Pancasila juga mampu menjadi penghubung antara ketegangan yang terjadi pada golongan pendukung agama dan negara. Hingga muncul sosok ulama dan sekaligus umara yang mampu meredam konflik antara agama dan negara, yaitu KH. Achmad Siddiq. KH. Achmad Siddiq sebagai sosok Kiai kharismatik yang dimiliki Nahdlatul Ulama mampu menjadi bintang yang dapat memersatukan dan menyelaraskan antara hubungan agama dan negara. Pengkajian agama dan negara dengan mengkaji pemikiran dari KH. Achmad Siddiq setidaknya menjadi referensi saat ini dengan semakin maraknya intoleransi yang terjadi. Dari pemikirannya yang cemerlang, Pancaila akhirnya diterima sebagai asas tunggal negara. Jenis penelitian yang digunakan adalah kepustakaan, yang memusatkan serta membatasi kegiatannya pada kepustakaan untuk memperoleh data tanpa melakukan riset di lapangan. Penelitian ini memperoleh kesimpulan; 1) KH. Achmad Siddiq mampu menjadi sosok yang dapat menghipnotis umat Islam khususnya warga Nahdliyin untuk menerima Pancasila sebagai asas tunggal organisasi dan negara. Hal tersebut menjadi rujukan umat beragama (Islam) khususnya warga NU dalam bernegara. 2) Mengenai kosep hubungan agama dan negara di Indonesia, dikenal dengan konsep Tri Ukhuwah. Pertama, Ukhuwwah Islamiyah, yaitu ukhuwah yang tumbuh dan berkembang karena persamaan keamanan atau keagamaan, baik di tingkat nasional maupun internasional. Kedua, Ukhuwah Wataniyyah, yaitu ukhuwah yang tumbuh dan berkembang atas dasar rasa nasionalisme. Ketiga, Ukhuwwah Insaniyah (basyariyyah), yaitu ukhuwah yang tumbuh dan berkembang atas dasar kemanusiaan.